Nivel de Adicción a las Redes Sociales en los Estudiantes de los Grados de Bachillerato en una Institución educativa de La Unión Valle (2024)
The objective of this research is to study the level of addiction to social networks in the Students of the Baccalaureate Degrees of the Argemiro Escobar Cardona Educational Institution of La Unión Valle. The research design is non5 experimental, cross-sectional, correlational. The instrument used to measure the variables was the Social Network Addiction Questionnaire (ARS) by (Echeburúa & de Corral, 2010) in order to know the relevant factors in addiction to RS and correlate them and know the level of addiction. of the students of the Educational Institution. The sample was made up of 40 students of both sexes and from the Institution's high school degrees, aged between 13 and 18 years. The results analyzed with the Power Bi software showed a medium level prevalence of addiction to social networks with 60%, while 35% of those surveyed showed a high rate of addiction compared to 5% of high school students. With a low level of addiction to RS, results that were correlated with a sociodemographic sheet, finding the importance of family and control in adolescent students.